ECONOMIC ASPECTS OF REGIONAL MANAGEMENT OF INNOVATIVE DEVELOPMENT OF TRAVEL ENTERPRISES - Kornilova, N. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. The paper discusses the economic aspects of the innovative development of travel enterprise. The primary conditions of this development are defined. In particular, the essence of “resultant” type of management for the creative development of travel company is debated. A general scheme of an interaction of economic agents in the control system of innovative development of tourist business is presented. Purpose of the article is a further study of economic aspects of innovative development of regional tourism market. Results. The following features if innovates governance were defined: Availability of material resources. These include almost any object, complex object, an image or an idea, which can cause a consumer interest in travel services. Availability of investment resources. In general, an investment in tourism industry means the temporary abandonment of resource consumption for the purpose of increasing the revenues in the future. Availability of labor resources. The importance of labor is growing due to nature of the tourist product and its distribution. Originality. Despite the large number of studies, there are currently no unified methodological approach to determining the economic essence of innovation enterprises of the travel industry. This paper broadens poorly described features of the economy innovation of tourism enterprises. It helps to ensure its long-term existence and stability of the market in terms of formation and development of the national economy. Conclusion. It is stated, that as the object of the travel market management, the efficiency as a complex category should be considered. At the same time, the main direction of innovative development of tourism at the regional level is the formation of its social dimension through the sustainable growth of economic indicators and the rational use of the economic potential of the region.